The effect of SARS‐CoV‐2 infection on cardiac function in post‐COVID‐19 survivors: A systematic review and meta‐analysis. Issue 1 (28th November 2022) - Rahmati, Masoud; Koyanagi, Ai; Banitalebi, Ebrahim; Yon, Dong Keon; Lee, Seung Won; Il Shin, Jae; Smith, Lee
Abstract: The longitudinal trajectories of cardiac structure and function following SARS‐CoV‐2 infection are unclear. Therefore, this meta‐analysis aims to elucidate the effect of SARS‐CoV‐2 infection on cardiac function in coronavirus disease 2019 (COVID‐19) survivors after recovery. PubMed/MEDLINE, CENTRAL, and EMBASE were systematically searched for articles published up to 1st August 2022. A systematic review and meta‐analysis were performed to calculate the pooled effects size and 95% confidence interval of each outcome. A total of 21 studies including 2394 individuals (1436 post‐COVID‐19 cases and 958 controls) were included in the present meta‐analysis. The pooled analyses compared with control groups showed a significant association between post‐COVID‐19 and reduced left ventricular ejection fraction (LV EF), LV end‐diastolic volume (LV EDV), LV stroke volume (LV SV), mitral annular plane systolic excursion (MAPSE), global longitudinal strain, right ventricular EF (RV EF), RV EDV, RV ESV, RV SV, tricuspid annular plane systolic excursion, and increased LV mass. Subgroup analysis based on the severity of COVID‐19 in the acute phase and subsequent chronic outcomes revealed that LV EF, MAPSE, RV EF, and RV ESV only decreased in studies including patients with a history of intensive care unit admission. Cardiac impairment after SARS‐CoV‐2 infection persisted in recovered COVID‐19 patients even after 1 year. Future studies are warranted to determine the biological mechanisms underlying the long‐term cardiovascular consequences of COVID‐19.